Application of iron-rich slag to capture carbon dioxide gas through direct gas-solid carbonation - F. Abdul; R.F. Rahman; K.A. Purwanto; F.I. Ma'ruf; Y. Setiyorini; V.A. Setyowati; S. Pintowantoro (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVE: The nickel processing industry has always been related with the issue of carbón dioxide emission. The production of carbon dioxide occurs at different phases of nickel processing, from pretreatment to smelting and refining. In addition to offgas, the nickel processing sector also produces solid waste known as slag, which is a byproduct of both smelting and refining processes. One of the slags in the nickel industry is known to contain iron, which is dominant compared to other elements. The primary objective of this study is to investigate the process of carbon dioxide capture by utilizing iron-rich slag derived from the nickel processing industry. The aim is to assess the feasibility of applying iron-rich slag from nickel smelters in the solid carbonation gas process for carbon dioxide capture, focusing on chemical reactions and overall kinetics.METHODS: The iron-rich slag analyzed in this study contains a significant amount of iron oxide. It is theoretically anticipated that the iron oxide content in iron-rich slag could potentially sequester carbon dioxide. The study commenced by preparing the materials, undergoing the carbonation process, and then conducting various characterizations including X-ray diffractometer analysis and thermal gravimetric analysis. Additionally, calculations were performed to determine the percentage of carbon dioxide in the sample and the efficiency of carbonation. The kinetics analysis was also carried out using several models, such as mass transport, chemical reaction, and diffusion-controlled model to estimate the carbón dioxide capture mechanism that occurs.FINDING: The carbon dioxide capture capacity of the iron-rich slag from the ferronickel industry is somewhat limited, albeit still relatively modest. Iron-rich slag was effectively utilized to capture carbon dioxide after thorough analysis. After undergoing a carbonation process for a duration of 4 hours, the percentage of carbon dioxide in the slag witnessed a significant increase, rising from an initial value of 0.28 percent to 1.12 percent. The capture of carbón dioxide gas is due to the reaction between silicate with carbón dioxide gas and water vapor to form siderite. The iron-rich slag operates under the diffusion-controlled model when it comes to capturing carbon dioxide.CONCLUSION: Iron-rich slag is reported to capture carbón dioxide at 175 degrees celsius with carbón dioxide and water vapor condition, which is proven both from thermodynamic calculations and experiments. Iron(II) carbonate is a carbonate compound generated by the carbón dioxide capture reaction by iron-rich slag. However, the stability of iron(II) carbonate in carbón dioxide and water vapor atmosphere is something that needs to be considered in future research. Further investigation can be conducted in the future to explore the potential of utilizing iron-rich slag for capturing carbon dioxide gas, building upon the findings of this preliminary study.